PARTISIPASI POLITIK UMAT KRISTEN SEBAGAI MISI GEREJA DALAM MEWARTAKAN ETIKA KRISTEN DI INDONESIA - Shintikhe Einstein Paramban; Jolianus, Adolpina, Oktaviani Indan (CV. Adiba Aisha Amira, 2024)
This study aims to discuss the importance of the church's political participation in its mission as a preacher of Christian ethics in society. The research method used is qualitative descriptive research method. What is qualitative research? It is social in nature by looking at various phenomena and behavior of animals and humans which are the objects of research. A qualitative approach is a method used to describe and describe the things being studied in detail. Researchers use a qualitative approach because it is considered appropriate and makes it easier to obtain data in the field regarding the problem being studied. So the following results were found: The Church's mission is to proclaim the principle of kindness to others, The mission of the Church is to declare that the most general principle of Church social education is the principle of general welfare (Bonham Commune); the mission of the Church is to declare the principle of solidarity; It is a declaration of defense of dignity. , and the mission of the Church to proclaim the principle of rejection of violence